A qualitative exploration of parental perspectives on quality of care for children with serious illnesses - Ang, Felicia Jia Ler; Chow, Cristelle Chu-Tian; Chong, Poh Heng; Tan, Teresa Shu Zhen; Amin, Zubair; Buang, Siti Nur Hanim; Finkelstein, Eric A. (Frontiers in Pediatrics, 2023)
Introduction: Being responsive to end-users is essential to good care. Limited in-depth exploration of parental perspectives on care received by children over the course of serious illness has hindered the development of process measures to evaluate quality of care. Our objective was to identify the key process indicators prioritized by parents in the care of seriously ill young children and develop a framework to guide assessment of quality of care. Methods: This qualitative study followed Charmaz’s Constructivist Grounded Theory. In-depth semi-structured interviews were conducted with parents of young children with serious illness in Singapore. Participants were sampled across various healthcare settings, children’s ages, and illness categories. Theoretical sampling and constant comparative analysis were used to generate initial, focused, and theoretical codes, which informed construction of a conceptual framework. Results: 31 parents participated from July 2021 to February 2022. Initial and focused coding generated 64 quality of care indicators describing key care practices, interactions, and procedures. Indicators were categorized under four themes: 1. efficient healthcare structures and standards, 2. professional qualities of healthcare workers, 3. supporting parent-caregivers, and 4. collaborative and holistic care. Theoretical coding led to the development of the “PaRental perspectives on qualIty of care for Children with sErious iLlnESSes (PRICELESS)” framework which summarizes elements contributing to the parental perception of quality of care. Discussion: The identified process indicators will facilitate the development of standardised parent-reported measures for assessing service quality and benchmarking among providers. The framework provides overall guidance for conceiving quality improvement initiatives.